2021
DOI: 10.3390/cells10081918
|View full text |Cite
|
Sign up to set email alerts
|

Epsins Negatively Regulate Aortic Endothelial Cell Function by Augmenting Inflammatory Signaling

Abstract: Background: The endothelial epsin 1 and 2 endocytic adaptor proteins play an important role in atherosclerosis by regulating the degradation of the calcium release channel inositol 1,4,5-trisphosphate receptor type 1 (IP3R1). In this study, we sought to identify additional targets responsible for epsin-mediated atherosclerotic endothelial cell activation and inflammation in vitro and in vivo. Methods: Atherosclerotic ApoE−/− mice and ApoE−/− mice with an endothelial cell-specific deletion of epsin 1 on a globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…As we show that silencing of lesional macrophage Epsins reduces necrotic core size, we reasoned that inhibiting Epsins may reinforce efferocytosis in macrophages, analogous to our observations in DKO macrophages (Brophy et al, 2019) given that efferocytosis plays a central role in regulating necrotic core formation (Gerlach et al, 2021; Kojima et al, 2017; Thorp et al, 2008). Despite the fact that S2P-NPs have been shown to only negligibly target the endothelium (Tao et al, 2020), whether S2PNP-siEpsin1/2 prohibits endothelial Epsins to synergistically curb atherosclerosis may require further investigation as deletion of endothelial Epsins also reduces inflammation and atherogenesis (Dong et al, 2020; Dong et al, 2021). Interestingly, we did not observe significant changes of the lipid profiles in the plasma from S2PNP-siCtrl and S2PNP-siEpsin1/2 treated ApoE -/- mice, suggesting either a minor liver targeting by S2PNP-siEpsin1/2 or that S2PNP-siEpsin1/2-mediated silencing of Epsins in liver could be inconsequential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we show that silencing of lesional macrophage Epsins reduces necrotic core size, we reasoned that inhibiting Epsins may reinforce efferocytosis in macrophages, analogous to our observations in DKO macrophages (Brophy et al, 2019) given that efferocytosis plays a central role in regulating necrotic core formation (Gerlach et al, 2021; Kojima et al, 2017; Thorp et al, 2008). Despite the fact that S2P-NPs have been shown to only negligibly target the endothelium (Tao et al, 2020), whether S2PNP-siEpsin1/2 prohibits endothelial Epsins to synergistically curb atherosclerosis may require further investigation as deletion of endothelial Epsins also reduces inflammation and atherogenesis (Dong et al, 2020; Dong et al, 2021). Interestingly, we did not observe significant changes of the lipid profiles in the plasma from S2PNP-siCtrl and S2PNP-siEpsin1/2 treated ApoE -/- mice, suggesting either a minor liver targeting by S2PNP-siEpsin1/2 or that S2PNP-siEpsin1/2-mediated silencing of Epsins in liver could be inconsequential.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their multifaceted functions, our previous work demonstrates that Epsins possess a vast degree of specificity and selectivity in choosing their binding partners. Therefore, the actions of Epsins are cell context-dependent (Brophy et al, 2019; Chang et al, 2015; Chen et al, 2009; Dong et al, 2020; Dong et al, 2021; Liu et al, 2014; Pasula et al, 2012; Tessneer et al, 2014). Notably, we demonstrated that myeloid-specific Epsins loss downregulated inflammation and impeded atheroma formation in an atherogenic mouse model by stabilizing macrophage LRP-1 (Brophy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that atherosclerotic plaques can be significantly reduced by API peptide administration (Figure 7). However, we could not completely rule out the possibility that some of the API peptide targeted macrophages, which could provide additional anti-inflammatory benefits 30,[42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that epsins bind to numerous receptors ( e.g., IP3R1, TNFR1, TLR2/4, and LRP1) via the UIM domain 30, 4244 . This suggests that epsin UIM was a critical domain to regulate inflammatory receptors, which was the basis for the development of our therapeutic peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation